(3eONd GdJMdjd Gdcejs - (3eMeO eMeO eMeO(B, (3GdNhdGfjs ((3GdGScfOQjI(B:s (3OGQ GdhaGA dOfjG GdWHGYI(B,s, 2007)
(3jVe eaghe hXjaI EOGQI GdfTGW GdEfJGLj hGdYedjGJ, GdLhGfH GdJfXjejI dEOGQI GdEfJGL hGdEfJGLjI, eOGNd OQGSI GdfTGW GdEfJGLj, GNJjGQ GdehbY, JUeje GdNW GdEfJGLj ef NdGd CeKdI eMdhdI, GdJfHD, LOhdI GdYedjGJ, EOGQI GdLhOIs
(3HjHdjhZQGajG(B: (3U U(B.305-307s
Keywords: (3EOGQI GdEfJGLs; (3VHW GdLhOIs